Mobile Touchless Fingerprint Acquisition And Enhancement System - Sagiroglu, Seref; Ulker, Mehtap; Arslan, Bilgehan (Ieee, 2020)
This study is concerned with the identification of individuals by using finger images captured by mobile devices. Within the scope of this study, the problems encountered in obtaining a fingerprint with mobile devices are initially determined and an apparatus is designed to solve and handle these problems. In order to analyze the feasibility, test the proposed apparatus and enhancement approach, the finger images captured by the mobile device are compared with the fingerprints collected by the sensor. The proposed approach is tested in the database composed of 104 fingerprints images captured from 52 different individuals. It has been seen that the fingerprints collected by the optical sensor are matched to the fingerprints captured by the apparatus integrated with the mobile device. The overall results of the proposed approach show performance with a FAR of 0.05% and FRR of 0.54% by using the apparatus designed.
IEEE Congress on Evolutionary Computation (CEC) as part of the IEEE World Congress on Computational Intelligence (IEEE WCCI) -- JUL 19-24, 2020 -- ELECTR NETWORK
Keywords: Fingerprint; touchless; mobile; enhancement; feature extraction; CLAHE; STFT